Concurrent Pneumocystis jirovecii and pulmonary histoplasmosis in an undiagnosed HIV patient. (26th January 2018) - Wahab, Ahsan; Chaudhary, Siddique; Khan, Mahin; Smith, Susan Jane
Abstract : Concurrent Pneumocystis jirovecii (PJ) and pulmonary histoplasmosis (PHP) are rare in a single HIV individual. We present a challenging case of concomitant PJ and PHP in a young HIV individual. A 44-year-old man presented to the emergency department with progressive pulmonary symptoms. He was hypoxic with bilateral pulmonary opacities on chest radiograph. CT of the chest showed a geographical pattern of ground-glass attenuation. He started receiving intravenous antibiotics in addition to oral Bactrim for suspected PJ. He also began receiving itraconazole, given suspected PHP with recent bat-droppings exposure. HIV test was positive, though history was negative; the CD4 count was 5 cells/mm 3 . Later, he developed respiratory failure without clinical improvement. First bronchoalveolar lavage (BAL) failed to confirm opportunistic pathogens. Repeat BAL revealed PJ but no Histoplasma. Histoplasma antigens were positive, confirming histoplasmosis. The patient died despite aggressive treatment with intravenous Bactrim and amphotericin B.